To be fit, or not to be: How influencer-driven advertising reinforces idealized beauty standards in adolescents - Feijoo, Beatriz; Vizcaíno-Verdú, Arantxa (Journal of Marketing Communications, 2024)
This study examines adolescents’ perceptions of body image advertising portrayed by social media influencers. Through discourse analysis, the research explores how participants interpret messages conveyed through influencer advertising content. The analysis reveals a discrepancy between adolescents’ understanding of ideal body representations and the descriptors used in advertising, shedding light on societal pressures surrounding body norms within social media. These findings underscore the pervasive influence of social media and advertising on adolescent body image constructs, highlighting the importance of cultivating critical advertising literacy skills among adolescents. Additionally, the study reveals that influencers affiliated with advertising perpetuate the stereotypical ideals of the body, emphasizing the need for educational and policymaker initiatives to promote healthy self-image.
Keywords: body image; adolescence; social media advertising; influencer; body positivity